Inhibitory effects of Gynura procumbens ethanolic extract on nitric oxide production and inducible nitric oxide synthase (iNOS) protein expression in macrophages - Tan, Jiah Ning; Syaratul Dalina Yusoff; Zakiah Jubri; Fhataheya Buang; Tan, Ze Song; Ameerah Budiono; Ibrahim Jantan; Roza Dianita; Endang Kumolosasi; Norazrina Azmi; Norsyahida Mohd Fauzi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Nitric oxide (NO) overproduction by inducible nitric oxide synthase (iNOS) may be associated with acute and chronic inflammations. Macrophages as important cells in the innate immune system are able to be stimulated and can lead to iNOS activation and excessive NO production. Gynura procumbens is a medicinal plant traditionally used in treating various ailments including inflammation but the mechanism of anti-inflammatory activity of this plant is still elusive. This study was carried out to investigate the anti-inflammatory therapeutic effects of Gynura procumbens ethanolic extract on NO production and iNOS protein expression in RAW 264.7 macrophages stimulated with lipopolysaccharide (LPS). Cell viability of RAW 264.7 macrophages treated with Gynura procumbens ethanolic extract was determined by MTT assay. NO production was determined by Griess assay following Gynura procumbens ethanolic extract treatment alone or in combination with LPS stimulation. Protein expression of iNOS was determined by western blot. RAW 264.7 macrophages viability of more than 90% was observed after 24 h treatment with Gynura procumbens ethanolic extract concentration range of 3.9 μg/mL to 500 μg/mL. Significant inhibition of NO production level has been identified in LPS-stimulated RAW 264.7 cells pre-treated with 250 μg/mL Gynura procumbens ethanolic extract (p<0.05) while all selected concentrations of Gynura procumbens ethanolic extract showed no significant alteration of NO production in the absence of LPS stimulation. Pre-treatment of 250 μg/mL Gynura procumbens ethanolic extract also demonstrated significant suppression of iNOS protein expression in LPS-stimulated RAW 264.7 cells (p<0.05). In conclusion, this study demonstrates that Gynura procumbens ethanolic extract exhibits anti-inflammatory potential through inhibition of NO production and iNOS protein expression in LPS-stimulated macrophages, suggesting that this plant could be further researched for its beneficial use in inflammatory disorders.